Spain the root and the flower : an interpretation of Spain and the Spanish people - Crow, John A. 1906-2001 (Berkeley University of California Press, 1985)
An interpretative history of Spain's culture, politics, traditions, and people from prehistoric times to the present, with particular concern for twentieth-century life, thought, and more.
The land: the people. -- The dark beginning. -- The cross, the crescent, and the star. -- The Christian kingdoms: cross and sword. -- Life in the medieval towns. -- The Spanish Renaissance. -- The golden age: politics and the social order. -- Belles-lettres in the golden age. -- The fine arts -- end of the golden age. -- The Bourbons. -- Main currents of Spanish thought (1870-1931) -- The political and social backgrounds of the Second Republic. -- The Spanish Republic (1931-1939) -- Communism and fascism in Spain. -- Valley of the fallen. -- Franco's legacy: order and progress. The economic miracle: The tourist industry, The economy, Salaries, prices, inflation ; Problem areas: Agriculture, Labor, Emigration. -- Spain today: the impossible dream a society in transition.
Includes bibliographical references (pages 435-439) and index.
Keywords: National characteristics, Spanish; Spain -- Civilization